2008
DOI: 10.1111/j.1464-410x.2008.07743.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive T1 bladder cancer: indications and rationale for radical cystectomy

Abstract: Invasive T1 bladder cancers are potentially lethal tumours with varying degrees of aggressiveness and progression. The management of invasive tumours can be very difficult and includes bladder‐sparing with transurethral resection and intravesical therapy, or a more aggressive approach with radical cystectomy. Certain clinical and pathological factors might provide some risk stratification for invasive T1 tumours, and might better direct the physician towards an earlier cystectomy for some patients. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…The high rates of progression and mortality seen in past studies have spurred clinicians to advocate early definitive, radical surgery for patients with HGT1 disease, particularly if they have certain high-risk features (2,8,11,12). Despite no randomized trials, multiple retrospective studies have shown advantages for disease-specific and overall survivals in patients treated with RC before muscle invasion occurs (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high rates of progression and mortality seen in past studies have spurred clinicians to advocate early definitive, radical surgery for patients with HGT1 disease, particularly if they have certain high-risk features (2,8,11,12). Despite no randomized trials, multiple retrospective studies have shown advantages for disease-specific and overall survivals in patients treated with RC before muscle invasion occurs (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…HGT1 bladder cancer represents a heterogeneous disease with varying phenotypes and outcomes, and currently no test or validated scoring system exists to predict which patients would benefit most from an early RC (8). Thus, this study re-examines the natural history of HGT1 bladder cancer by analyzing the recurrence and progression rates of a large cohort of patients initially diagnosed with HGT1 disease to determine if, in fact, the high incidence of disease progression and death due to bladder cancer is still witnessed in a more contemporary treatment era.…”
Section: Introductionmentioning
confidence: 99%
“…2,23 As a result, some studies advocate initial cystectomy based on the perceived acceptable morbidity and a 5-year disease-specific survival rate of 80% to 90%. [24][25][26][27][28] However, the paucity of effective conservative treatment alternatives for stage T1 disease may be misinterpreted as an immediate mortality risk in patients who continue to exhibit organ-confined disease. As we will discuss later, an initial trial of BCG rather than immediate cystectomy appears justified in almost all initial T1Hg cases without undue risk, since progression within the first six months is rare (less than 4%).…”
Section: Patient Counsellingmentioning
confidence: 99%
“…T1 tumors are generally high grade, with a high risk of progression and/or metastasis. Progression rate is 20 to 40% in low grade T1 tumors treated by TUR only (Nieder et al, 2005;Stein and Penson, 2008). Progression and recurrence rates of high-grade T1 tumors are reported to be 60% and 80%, respectively (Heney, 1992).…”
Section: Introductionmentioning
confidence: 99%